2017
DOI: 10.1155/2017/9593631
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Informed Consent for Cataract Surgery: A Randomized Controlled Trial

Abstract: Purpose. To investigate whether adding video assistance to traditional verbal informed consent advisement improved satisfaction among cataract surgery patients. Methods. This trial enrolled 80 Chinese patients with age-related cataracts scheduled to undergo unilateral phacoemulsification surgery. Patients were randomized into two groups: the video group watched video explaining cataract-related consent information and rewatched specific segments of the video at their own discretion, before receiving traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Nonetheless, no studies reported that the use of patient’s education videos resulted in a decreased patient’s satisfaction or comprehension. 8 11 , 13 This finding suggests that the incorporation of educational videos into the informed consent process can be equally as effective as traditional methods of surgical counseling. In our study, we also found that the amount of time required to complete the consent process for the MIC group was significantly lower than the control group, suggesting that videos can help improve efficiency.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nonetheless, no studies reported that the use of patient’s education videos resulted in a decreased patient’s satisfaction or comprehension. 8 11 , 13 This finding suggests that the incorporation of educational videos into the informed consent process can be equally as effective as traditional methods of surgical counseling. In our study, we also found that the amount of time required to complete the consent process for the MIC group was significantly lower than the control group, suggesting that videos can help improve efficiency.…”
Section: Discussionmentioning
confidence: 95%
“… 13 However, there is some disparity in the literature, as several other studies found significant improvements in comprehension for those receiving video-based information. 8 11 Zhang et al, 8 who performed a similar study examining cataract surgery candidates, reported a satisfaction of 86% for those who viewed a video and 65% ( P =0.035) for those who did not. These variable findings may be attributed to external factors such as quality of the video used, educational level of the patient population sampled, and methods for evaluating outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is even more delicate in pediatric surgery, when caregivers make decisions for their children. Current research on using multimedia presentations and videos as decision aids for informed primarily focused on adult patients [11][12][13]. Zieren et al used a video before inguinal hernia repair in adult in an effort to shorten the time a surgeon needs to invest into the informed consent discussion [11].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In most cases in which videos were used in the consent process, there were improvements in patient satisfaction, 9,11,[13][14][15]20 patient knowledge, or both. 7,8,10,[13][14][15][16][19][20][21]23 Several studies have demonstrated that videos take the same amount of time as standard processes 19 or even save time, 9,12,21 and reduce patient anxiety. 11 Mohs micrographic surgery is a complex multistage procedure, with waiting times in between stages, depending on the extent of the cancer mass before surgical repair of the defect.…”
Section: Introductionmentioning
confidence: 99%